2022
DOI: 10.1039/d2nr03121c
|View full text |Cite
|
Sign up to set email alerts
|

Spatially confined growth of carbon nanotubes in the pore channels of microporous ceramic supports with improved filtration efficiency

Abstract: Carbon nanotubes (CNTs) with high degrees of uniformity, orientation and controlled dimensions on porous supports are highly desirable for various application such as separation of O/W emulsions and air purification....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…The use of ceramic membranes in industrial filtration typically requires high‐pressure air back‐flushing to remove deposited dust layers 37–39 . However, this can expose the ceramic membrane to thermal shock, resulting in cracks on the surface of ceramic membrane.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of ceramic membranes in industrial filtration typically requires high‐pressure air back‐flushing to remove deposited dust layers 37–39 . However, this can expose the ceramic membrane to thermal shock, resulting in cracks on the surface of ceramic membrane.…”
Section: Resultsmentioning
confidence: 99%
“…The use of ceramic membranes in industrial filtration typically requires high-pressure air back-flushing to remove deposited dust layers. [37][38][39] However, this can expose the ceramic membrane to thermal shock, resulting in cracks on the surface of ceramic membrane. To investigate the thermal shock resistance of the TCS support, which largely determines the structural properties of the ceramic membrane, its radial crushing strength was measured (Figure 2A).…”
Section: Thermal Shock and Acid Corrosion Resistance Of Tcs Supportmentioning
confidence: 99%
“…Li et al [ 23 ] studied the self-organized patterns of microporous ceramics, which were characterized by an arbitrarily functional circuit design and precise fixation. Yuan et al [ 24 ] provided results of the preparation and filtration application of CNTs on porous materials. Zhou et al [ 25 ] found that a microporous ceramic filter membrane had a large change in permeate flux during the initial stage of filtration and gradually tended to be stable.…”
Section: Introductionmentioning
confidence: 99%
“…Several techniques have been applied to fabricate fibrous materials based on web-like structures to further enhance the separation performance. Building blocks like carbon nanotubes (5 to 10 nm) or cellulose nanocrystals (∼10 nm) are commonly used, based on the deposition method, to construct porous filters. But the poor continuity and dispersity inevitably cause random-deposited nonwovens with compact stacking structures rather than organized networks, finally leading to the decreased flux. Nevertheless, electrospinning technology is easily able to synthesize continuous nanofibers on a large scale, and the fabricated nanofiber membranes (NFMs) exhibit enhanced permeability due to their high porosities (>80%). Despite that, electrospun NFMs have limited removal efficiency on account of pseudonanoscale diameters (0.2–2 μm) and micron-sized pores (usually >3 μm) caused by the unpredictable construction manner.…”
mentioning
confidence: 99%